Effect of the Mechanical and Thermal Stresses of Rotating Blades - AL-sahib, Nabeel K. (Al-Khwarizmi Engineering Journal, 2007)
Rotating blades are the important parts in gas turbines. Hence, an accurate mathematical estimation (F.E.M) of the stresses and deformations characteristics was required in the design applications to avoid failure. In recent year’s there are researchers interest in the effect of temperature on solid bodies has greatly increased, The main of this study investigated the thermal and rotational effects. So, the thermal stresses due to high pressure and temperature are studies, also determine the steady state stresses and deformations of rotating blades due to mechanical effect. Many parameters such as thickness and centre of rotating are investigated in this paper. The study results can ensure good recommendation for the effect of the mechanical and thermal stresses of rotary blades.